Prisons Ordinance (1952) : A short survey / Abd. Rahman Abdullah - Abdullah, Abd. Rahman (Faculty of Law, 1985)
This paper was written in consequence of a series of' incidents involving questions on security of prisons in Malaysia. The first incident was the hostage drama in Pudu Prison on October 17th 22nd, 1987; which was followed by Puan Mariana hostage drama 78 days at the Kuantan prison.